Evaluation of direct immunofluorescent method in the detection of Pneumocystis jiroveci among patients with lower respiratory tract infections - Manahil M. Yehia; Asmaa Z. Sheetawy; Zainalabideen A. Abdulla (University of Mosul, 2019)
Objective: Evaluate the use of direct immunofluorescent method in the detection of Pneumocystis jiroveci from induced sputum of patients with LRT infections.   Patients and methods: Thirty patients with LRT infections were included (24 patients were immunocompromised and 6 immunocompetent). The present study conducted for 6 months from January-June, 2011. Smears were prepared from their induced sputa and stained with direct fluorescent antibody stain, then examined under fluorescent microscope. Results: Sputum of 5(16.7%) patients revealed positive results for the presence of P. jiroveci and all of them were immunocompromised (two acute myloid leukemia, one acute lymphoid leukemia, one non-Hodgkin's lymphoma, and one asthma under long coarse of corticosteroid therapy). Conclusion: Direct fluorescent antibody technique is more sensitive than the conventional methods for the detection of P. jiroveci in LRT infections. Keywords: Pneumocystis pneumoniae, Pneumocystis jiroveci, immunocompromised patients.